Additional file 2 of Genetic mapping and QTL analysis for peanut smut resistance - De Blas, Francisco Javier (2021)
Fil: De Blas, Francisco Javier. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias; Argentina.